The role of STEM education in reducing educational inequalities: A case study in the Northern Mountainous Provinces of Vietnam - Quang, Linh Nguyen; Thu, Huong Le Thi (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the role of STEM education in reducing educational inequalities in the northern mountainous provinces of Vietnam. The study’s primary goal is to determine how and to what degree STEM education may improve student learning possibilities, and hence reduce educational inequalities. The study used in-depth interviews with teachers and students, in combination with mathematical statistics. The findings from the study show that teachers and students in the northern mountainous provinces of Vietnam have a positive perception of STEM education, particularly in that STEM education can reduce educational inequalities. The study also highlights some challenges such as a lack of resources, facilities, or support. To promote the effectiveness of STEM education while reducing educational inequalities, the conclusion of the study emphasizes the importance of investing in facilities, fostering teachers, strengthening online support tools (sample lectures, videos teaching STEM design and production), and more active community participation.